2022
DOI: 10.1111/1467-9566.13508
|View full text |Cite
|
Sign up to set email alerts
|

Assembling care: How nurses organise care in uncharted territory and in times of pandemic

Abstract: This article draws on ethnographic research to conceptualise how nurses mobilise assemblages of caring to organise and deliver COVID care; particularly so by reorganising organisational infrastructures and practices of safe and good care. Based on participatory observations, interviews and nurse diaries, all collected during the early phase of the pandemic, the research shows how the organising work of nurses unfolds at different health-care layers: in the daily care for patients and their families, in the coo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 62 publications
(75 reference statements)
0
15
0
Order By: Relevance
“…Our ndings show how collaboration across professional and organisational boundaries created learning processes and resilience (33). This demonstrates that whilst clinicians were reacting to the disruption they were proactively seeking strategies to create a resilient service that re ected the complexity of the emerging sequelae post COVID-19 (32).…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Our ndings show how collaboration across professional and organisational boundaries created learning processes and resilience (33). This demonstrates that whilst clinicians were reacting to the disruption they were proactively seeking strategies to create a resilient service that re ected the complexity of the emerging sequelae post COVID-19 (32).…”
Section: Discussionmentioning
confidence: 70%
“…As events unfolded, situated resilience emerged as clinicians interacted with and assembled sociotechnical resources (knowledge, skills, staff, IT) to identify what needed to be done to set up follow-up provision for patients (32). For services to be set-up, it was dependant on scaling-up the response from the micro-level to the meso-level.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, because the writing of dairies can be time-consuming and frustrating (Meth, 2003) the use of more creative approaches such as audio or video may be more appealing to participants (Buchwald et al, 2009). Indeed, Kuijper et al (2022) in their study about how nurses mobilise assemblages of caring to organise and deliver COVID-19 care found that keeping a diary may be burdensome for participants, in particular in times of crisis. Further, writing a diary can be a complex task to participants when they suffer from a health condition (Milligan et al, 2005).…”
Section: Sensory Intangibilitymentioning
confidence: 99%
“…Indeed, Kuijper et al. (2022) in their study about how nurses mobilise assemblages of caring to organise and deliver COVID‐19 care found that keeping a diary may be burdensome for participants, in particular in times of crisis. Further, writing a diary can be a complex task to participants when they suffer from a health condition (Milligan et al., 2005).…”
Section: Sensory Intangibilitymentioning
confidence: 99%
“…Shortages of nurses put healthcare systems under pressure, as governments are confronted with a mounting backlog of non-COVID care and rising care demands due to demographic transition. The COVID-pandemic has put nurses in the spotlight, and, especially in the first months, made nurses into a celebrated profession (Croft and Chauhan, 2021; Mohammed et al ., 2021; Kuijper et al ., 2022). The COVID-pandemic also elucidated the looming crisis of nurse workforce shortage, accelerated further by the pandemic.…”
Section: Introductionmentioning
confidence: 99%